2014
DOI: 10.1086/674358
|View full text |Cite
|
Sign up to set email alerts
|

Coflowering Community Context Influences Female Fitness and Alters the Adaptive Value of Flower Longevity inMimulus guttatus

Abstract: A major goal in evolutionary biology is to incorporate the complexity of multispecies interactions into our understanding of microevolutionary processes within populations. Although considerable work has been done on antagonistic interactions (e.g., plant-herbivore), little attention has been paid to the evolutionary implications of context dependency in mutualistic interactions (e.g., plant-pollinator). In this study, we use seep communities to evaluate how coflowering species richness affects key aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 97 publications
2
67
2
Order By: Relevance
“…Data available for Yr 2 on our sites showed that soil volumetric water content descended from 38.8% on HIGH to 5.0% on LOW (S2 Table). Lower water availability and higher temperatures at lower elevations would increase floral physiological costs, which is turn would diminish the chances of increasing reproductive success due to resource limitation for producing seeds and fruits [23]. Indeed, the capacity for rapid plastic adjustment of flower longevity under drought might have been selected in R .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data available for Yr 2 on our sites showed that soil volumetric water content descended from 38.8% on HIGH to 5.0% on LOW (S2 Table). Lower water availability and higher temperatures at lower elevations would increase floral physiological costs, which is turn would diminish the chances of increasing reproductive success due to resource limitation for producing seeds and fruits [23]. Indeed, the capacity for rapid plastic adjustment of flower longevity under drought might have been selected in R .…”
Section: Discussionmentioning
confidence: 99%
“…Flowers that have the capacity to stay open for long periods of time in general allow more time for pollinator visits to accumulate [20,21] and thus can increase the probability of successful pollination when pollinator availability reaches a critical threshold. Nevertheless, physiological costs associated with transpiration, respiration and nectar production in flowers can drain resources for later fruit and seed set [22,23] and thus place limits on flower longevity, such that pollinator availability in natural populations is not the only factor molding flower longevity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant material.-We planted 30 M. guttatus seeds each from a different maternal plant from population 1 (in Arceo-Go´mez and Ashman [2014]) at the McLaughlin Natural Reserve in northern California. Twentyeight of these plants were designated pollen recipients and functioned as self pollen donors, and the remaining two functioned as outcross pollen donors.…”
Section: Methodsmentioning
confidence: 99%
“…When HP treatment had an overall significant effect we conducted preplanned linear contrasts (Rosenthal andRosnow 1985, Abelson andPrentice 1997) to test specific hypotheses regarding the presence and arrival time of HP receipt (e.g., Strauss and Murch 2004, Arceo-Go´mez and Ashman 2011, 2014. We accounted for variation among recipients by including plant as a random factor in the models but did not test its significance.…”
Section: Methodsmentioning
confidence: 99%